2015
DOI: 10.1259/bjr.20140767
|View full text |Cite
|
Sign up to set email alerts
|

A review of cross-sectional imaging, ultrasound and nuclear medicine utilization patterns in paediatric patients in Ireland, 2003–12

Abstract: Objective: Recent trends in paediatric imaging have been examined in Australia and the USA. Such literature in Europe is sparse, incomprehensive and outdated. This research investigated (1) population-based trends in the use of advanced medical imaging in children in Ireland from 2003 to 2012; (2) its use across age and gender; and (3) the most commonly performed examinations within each modality. Methods: A retrospective cohort analysis study was carried out within Irish paediatric hospitals. All CT, MRI, ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Although some of this increase is likely the re- sult of referral patterns, the increased ease and prevalence of neuroimaging also likely contributed to the rise in cases. [20][21][22] MRI utilization has increased fourfold in the US and Canada, going from 16 cases per 1000 person-years in 2000 to 64 cases per 1000 person-years in 2016, 23 and we suspect iLGG will be encountered more frequently in the future by all neurosurgical oncologists. Given our findings, we believe these tumors can be safely removed and patients can benefit from early surgical intervention.…”
Section: Discussionmentioning
confidence: 86%
“…Although some of this increase is likely the re- sult of referral patterns, the increased ease and prevalence of neuroimaging also likely contributed to the rise in cases. [20][21][22] MRI utilization has increased fourfold in the US and Canada, going from 16 cases per 1000 person-years in 2000 to 64 cases per 1000 person-years in 2016, 23 and we suspect iLGG will be encountered more frequently in the future by all neurosurgical oncologists. Given our findings, we believe these tumors can be safely removed and patients can benefit from early surgical intervention.…”
Section: Discussionmentioning
confidence: 86%
“…The number of diagnostic radiologic procedures performed worldwide increased dramatically in the past decades, resulting in an increased effective annual dose per-capita. 5 These temporal changes were also seen in children, [6][7][8][9] although some studies report a stabilization in CT exams performed since approximately 2000. 6,9 In the pediatric population, radiation exposure dose is of greater importance due to increased relative risk for radiation-related cancer than in adults.…”
Section: Introductionmentioning
confidence: 93%
“…A few studies revealed that the quantity of MRI scanners and utilization increased rapidly in many countries, such as the United States (3), Canada (4,5), South Korea (6), and Ireland (7). Research conducted by Luyang He(8) found a high growth rate of absolute device number in China, but the overutilization and underutilization of MRI scanners might coexist.…”
Section: Introductionmentioning
confidence: 99%